Peran Kegiatan Kepramukaan Dalam Menanamkan Sikap Solidaritas Organik Pada Siswa Kelas X SMA Negeri 1 Kayan Hulu - Sriyati m (Universitas Tanjungpura, 2020)
The purpose of this research is to know the role of scout leader by planting organic solidarity, the method used is qualitative descriptive. Data collection techniques are observation, interview and documentation study, data collection tools guide observation, interview, and documentation. The results of research through the moral sense, all team members observe the material provided scoutmaster, mutual trust, discussion or deliberation trying to receive opinions and always accept what the decision and is ready to accept criticism, accept feedback and criticism from the other members, through the emotional experience, the role of scoutmaster realized learners to always be able to hold back the emotion and not reckless, dare to give presumption that feels right and can be held responsible or what you do, do not break the rules set by senior and promised to anyone, including the tasks given in planting organic solidarity in SMA Negeri 1 Kayan Hulu.